PENERAPAN UNDANG-UNDANG NOMOR 18 TAHUN 2008 TENTANG PENGELOLAAN SAMPAH PADA PERUSAHAAN AIR MINERAL DALAM KEMASAN (Studi Kasus Penggunaan Kemasan Galon Sekali Pakai) - Eli Sanur Nasution (2023)
This research is intended to examine how Law Number 18 of 2008 regulates the role of single-use gallon-packaged Mineral Water Companies (AMDK) in the management of products or packaging waste they produce and the responsibility of producers towards product packaging and packaging waste. This research is motivated by various problems related to packaging waste generated by disposable gallon packaging manufacturers, increased environmental burden due to the accumulation of disposable gallon waste and then the producer's small responsibility for the waste that the product produces. This study uses a normative juridical approach. The results of the study show that there is a need for extended responsibility to producers for products that will be marketed to consumers. Law No. 18 of 2008 was strengthened again with the birth of the Road Map of the Ministry of Environment and Forestry (KLHK) No. 75 of 2019 concerning the Roadmap for Waste Reduction where currently the government has a 30% waste reduction program for the next 10 years, it seems that the spirit of waste reduction carried out by the government is not heeded by single-use gallon packaging manufacturers, because the packaging used is not in accordance with the concept of 3R waste management (Reduce, Reuse, Recycle).